Out-of-pocket expenditures for HIV in the Dominican Republic: findings from a community-based participatory survey - Claire Chaumont; Carlo Oliveira; Enrique Chavez; Jaime Valencia; Pablo Villalobos Dintrans (Pan American Health Organization, 2019)
Objectives. The aim of this study was to estimate out-of-pocket expenditures incurred by individuals with HIV in the Dominican Republic. The study utilized different definitions and components for these expenditures and differentiated the results by wage ranges. Methods. Data was obtained from an in-person survey of people living with HIV. The study was developed and implemented in collaboration with Dominican grassroots organizations and networks of people with HIV, through a process of community-based participatory research. Results. The mean HIV-related expenditure reported by individuals in the sample in the last six months prior to the survey was in US$ 181; 15.4% of this total was spent for transportation and housing and costs to access the HIV facility. The mean expenditure reported by individuals for their current visit to an HIV center was US$ 10. These out-of-pocket expenditures exhibited regressivity, with lower-wage patients spending proportionally more to receive care. The results highlight the importance of considering other resources required to access treatment, such as lodging expenses and the time needed to travel to an HIV center and then to wait to be seen by a care provider. Conclusions. There should be more focus on expenditures made directly by people with HIV in the Dominican Republic so that these payments do not become a barrier to accessing health care. Using a community-based participatory design can ensure that such data can be leveraged to address the specific barriers to care that are faced by individuals with HIV.